2022
DOI: 10.3390/mca27030040
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Quasi-Newton Acceleration for Fluid-Structure Interaction

Abstract: We propose two enhancements of quasi-Newton methods used to accelerate coupling iterations for partitioned fluid-structure interaction. Quasi-Newton methods have been established as flexible, yet robust, efficient and accurate coupling methods of multi-physics simulations in general. The coupling library preCICE provides several variants, the so-called IQN-ILS method being the most commonly used. It uses input and output differences of the coupled solvers collected in previous iterations and time steps to appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…According to (6), f k+1 is the minimum of a one-dimensional function whose gradient is ⟨ g(x k ), s k ⟩/∥s k ∥. Due to the fact that this one-dimensional function also satisfies Condition 1, to estimate the numerator in (9), taking into account inequality (4), we obtain:…”
Section: Accelerating Properties Of Newton's Methods Under Conditions...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to (6), f k+1 is the minimum of a one-dimensional function whose gradient is ⟨ g(x k ), s k ⟩/∥s k ∥. Due to the fact that this one-dimensional function also satisfies Condition 1, to estimate the numerator in (9), taking into account inequality (4), we obtain:…”
Section: Accelerating Properties Of Newton's Methods Under Conditions...mentioning
confidence: 99%
“…Numerous studies on the convergence rate of Newton methods and quasi-Newton methods in the extremum region have been conducted, and some of them are given in [1][2][3][4][5][6][7][8]. The results obtained in [9,10] refer to the convergence rate of quasi-Newton minimization methods under the assumption that the method operates in the extremum area of the function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, it relied only on input–output data pairs collected within the current time step. Follow‐up research revealed, however, that using past time step data is very advantageous, but also challenging: an explicit reutilization of data pairs may suffer from rank deficiency and the dependency on the number of reused time steps—although both effects can be alleviated by proper filtering techniques 14,15 . An implicit incorporation via an updated Jacobian avoids these issues, but typically brings along a costly explicit Jacobian 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up research revealed, however, that using past time step data is very advantageous, but also challenging: an explicit reutilization of data pairs may suffer from rank deficiency and the dependency on the number of reused time steps-although both effects can be alleviated by proper filtering techniques. 14,15 An implicit incorporation via an updated Jacobian avoids these issues, but typically brings along a costly explicit Jacobian. 9,10 However, recent formulations circumventing this drawback were presented by Scheufele and Mehl 16 as well as Spenke et al.…”
Section: Introductionmentioning
confidence: 99%